The Effect Of Islamic Sharia Compliance, Corporate Governance, and Company Characteristics On CSR Disclosure - Saputri, Reza Septiana; Hafiza, Amanatu (Riau International Conference on Economics, Business and Accounting, 2025)
This study aims to examine the effect of Islamic sharia compliance, corporate governance proxied by independent commissioners, audit committees, managerial ownership and public ownership as well as company characteristics proxied by profitability, leverage and company size on CSR disclosure. The type of data used in this study is secondary data taken from annual reports and company sustainability reports. The objects used in this study were all companies that are participants in ISRA and listed on the IDX in 2017-2020. The sampling method used purposive sampling, so that a sample of 55 companies was obtained. The data analysis in this study used multiple linear regression analysis and SPSS version 28. The results of this study indicate that Islamic sharia compliance, independent commissioners, audit committees and leverage have a positive effect on CSR disclosure. Public ownership has an effect on CSR disclosure. Profitability and company size have a negative effect on CSR disclosure. While managerial ownership has no effect on CSR disclosure.